HOW NEWS COVERAGE OF NADIEM MAKARIM’S PUBLIC STATEMENT ON THE MERDEKA BELAJAR POLICY IN TEMPO CONSTRUCTED: FAIRCLOUGH’S THREE-DIMENSIONAL MODEL OF CDA - Andriani, Agis; Wanfa, Muhammad Ramdhan; Sri, Melisa (Journal of Pragmatics and Discourse Research, 2025)
This study analyses how news coverage of Nadiem Makarim’s public statement on the Merdeka Belajar policy in Tempo is constructed through Fairclough’s Three-Dimensional model. The objective is to reveal how ideology and power relations are communicated in this discourse. Employing Critical Discourse Analysis (CDA) as its methodological framework, data were collected with document analysis of a Tempo online article Bowen (2009) and examined through Fairclough’s three dimensions that include description (text analysis), interpretation (processing analysis), and explanation (social analysis). Findings show that Nadiem’s statement is represented as an urgency demanding government action that framed across all three CDA stages. At description level, lexical choices, nominalization, passivization, and transitivity foreground ideological framing and underscore governmental leadership in promoting transformative education. At interpretation level, media credibility is negotiated through the selection of news sources and a balance between subjective and objective reporting. At the explanation level, socio-cultural and political contexts, including the Minister’s self-image, ideological conflicts between progressive and conservative group, hierarchical power relation, and enduring traditional cultural values that shape and legitimize the policy discourse. Implications of this study highlight the pivotal role of language in building public trust and legitimizing transformative education reforms. This research offers valuable insights for policy makers, educators, and future CDA studies in educational contexts.